SOLVABILITY RATIO TO BOND RATING IN THE COMPANY PT. ADHI COMMUTER PROPERTIES AND SUBSIDIARIES IN 2021-2022 LISTED ON THE INDONESIAN STOCK EXCHANGE (BEI) - Fadli; Irada Sinta; Rico Nur Ilham; Muhammad Multazam; Frengki Putra Ramansyah (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
Bonds are an investment instrument that is in demand by both investors and issuers because they have a fixed income that comes from interest and principal debt. The solvency ratio is an important indicator in evaluating a company's ability to meet long-term financial obligations. This research aims to evaluate the effectiveness of the solvency ratio as a tool for measuring a company's ability to fulfill long-term obligations to the company PT. Adhi Commuter Properti and its subsidiaries listed on the Indonesia Stock Exchange. The research method used is descriptive qualitative by calculating the solvency ratio (Debt to Asset Ratio and Debt to Equity Ratio) from the financial report data of the company PT. Adhi Commuter Properti and subsidiaries that issued bonds in 2021 and 2022. This research evaluates the effectiveness of the solvency ratio as a tool for measuring the company's ability to fulfill its long-term obligations, using PT. Adhi Commuter Properti and Subsidiaries as a case study. The research method used is descriptive qualitative with data analysis from the annual financial reports of companies listed on the Indonesia Stock Exchange and the bond rating database from PT. PEFINDO for the 2021-2022 period. The results of the solvency ratio analysis show a decrease in the Debt to Asset Ratio (DAR) from 64.87% (2021) to 61.11% (2022), as well as a decrease in the Debt to Equity Ratio (DER) from 193.92% (2021) to 173 .84% (2022). This indicates better management of financial risks and possible reduction in interest expenses for the company. These changes provide investors with a positive indication regarding the company's financial stability and the potential for reducing financial risks associated with liabilities. In terms of bond ratings, PT. Adhi Commuter Properti maintains its idBBB rating in 2021 and 2022, demonstrating adequate ability to pay its financial obligations.